Written on the wind - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Blackstone legacy, 2022)
"From the steppes of Russia to the corridors of power in Washington, Natalia and Dimitri will fight against all odds to save the railroad and share the truth of what happened, but how can their newfound love survive the ordeal?"--